MANAJEMEN KOORDINASI DALAM PERSPEKTIF ISLAM: ANALISIS NILAI-NILAI QUR’ANI SEBAGAI FONDASI ORGANISASI - FEBRIANTI, RIKA (LPPM STAI Muhammadiyah Probolinggo, 2026)
Perspective of Islamic management, Qur’anic values serve as the fundamental basis for building ethical, effective, and sustainable organizational governance. This study aims to formulate a new paradigm of Islamic-based coordination management by positioning Qur’anic valuesparticularly justice, trustworthiness, accountability, consultation (shura), transparency, collaboration as both epistemological and operational frameworks in modern organizational management. This research employs a qualitative approach with a library research design, in which primary data are derived from the Qur’an and hadith, while secondary data are obtained from academic literature, journals, and previous studies. Data were collected through document review and systematic literature tracing, and analyzed using Qur’anic hermeneutics and content analysis through the stages of reduction, display, and conceptual synthesis. The findings reveal that integrating Qur’anic values generates a new paradigm of Islamic coordination management that is more comprehensive than conventional approaches. Justice is effective in distributing authority fairly and reducing internal conflict, trustworthiness and accountability strengthen moral legitimacy and public trust, while consultation functions as both a participatory decision-making mechanism and a tool for conflict resolution. These results highlight that challenges such as limited human resources, technological gaps, and conflict management issues can be addressed through an Islamic coordination management model. The study concludes that Qur’anic values are not merely supportive variables but constitute an epistemological foundation for organizational governance, with theoretical implications enriching Islamic management literature and practical implications offering strategic guidance for organizations to become more adaptive, sustainable, and competitive.